The Market for Retirement Products in Australia - Brunner, Gregory Gordon; Thorburn, Craig (World Bank, Washington, DC, 2012)
Australia introduced a mandatory retirement savings scheme in 1992. This built on pre-existing voluntary occupational plans. The new scheme has been very successful in expanding coverage and mobilizing large financial savings that are equal to close to 100 percent of GDP. However, Australia does not impose restrictions on payout options. The payout phase used to be dominated by lump sum withdrawals, which accounted for 80 percent of benefit payments as recently as 2002. But pension payments increased in recent years and now represent 45 percent of total payments. The vast majority of these pension payments take the form of term annuities and allocated annuities. The latter are similar to phased withdrawals in Chile but run for fixed terms of up to 25 years rather than for lifetime terms. The demand for life annuities and lifetime phased withdrawals is very limited. The paper discusses the factors that have shaped the pattern of demand for retirement products, including the availability of the universal age pension and the effect of clawback provisions, the impact of the high level of home ownership, and the widespread preference of retiring workers for reliance on self-annuitization. The paper also reviews the prudential regulation of superannuation funds and life insurance companies.